CD47 as a Potential Target to Therapy for Infectious Diseases - Lamin B. Cham; Tom Adomati; Fanghui Li; Murtaza Ali; Karl S. Lang (Antibodies, 2020)
The integrin associated protein (CD47) is a widely and moderately expressed glycoprotein in all healthy cells. Cancer cells are known to induce increased CD47 expression. Similar to cancer cells, all immune cells can upregulate their CD47 surface expression during infection. The CD47-SIRPa interaction induces an inhibitory effect on macrophages and dendritic cells (dendritic cells) while CD47-thrombospondin-signaling inhibits T cells. Therefore, the disruption of the CD47 interaction can mediate several biologic functions. Upon the blockade and knockout of CD47 reveals an immunosuppressive effect of CD47 during LCMV, influenza virus, HIV-1, mycobacterium tuberculosis, plasmodium and other bacterial pneumonia infections. In our recent study we shows that the blockade of CD47 using the anti-CD47 antibody increases the activation and effector function of macrophages, dendritic cells and T cells during viral infection. By enhancing both innate and adaptive immunity, CD47 blocking antibody promotes antiviral effect. Due to its broad mode of action, the immune-stimulatory effect derived from this antibody could be applicable in nonresolving and (re)emerging infections. The anti-CD47 antibody is currently under clinical trial for the treatment of cancer and could also have amenable therapeutic potential against infectious diseases. This review highlights the immunotherapeutic targeted role of CD47 in the infectious disease realm.